2013
DOI: 10.5897/ajar12.2099
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the choice of conservation agriculture practices adopted by smallholder cotton farmers in Zimbabwe

Abstract: Conservation agriculture (CA) has been widely promoted in Zimbabwe as an antidote to non-viable agricultural production and continual land degradation. However, the adoption process had been quite slow and has not yet entered into the exponential uptake phase. This study aimed at identifying factors that influence the level of adoption of CA components. A cluster analysis from results of a household survey administered to 146 households in Muzvezve II, Kadoma District, Zimbabwe identified five dominant CA stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Ownership of labour saving equipment such as rippers coupled with the prestige associated with owning such implements increased the likelihood of adopting CA. This result is consistent with studies such as Chomba (2004), Umar et al (2010), Mavunganidze et al (2013), and Lugandu, (2013) who found that ownership of productive assets increases the likelihood of adopting a given technology. As regards gender, the study revealed that men and women were more likely to adopt CA by ripping and CA basins respectively from among the various variants of CA being promoted by Conservation Agriculture Project (CAP).…”
Section: Literature Reviewsupporting
confidence: 82%
“…Ownership of labour saving equipment such as rippers coupled with the prestige associated with owning such implements increased the likelihood of adopting CA. This result is consistent with studies such as Chomba (2004), Umar et al (2010), Mavunganidze et al (2013), and Lugandu, (2013) who found that ownership of productive assets increases the likelihood of adopting a given technology. As regards gender, the study revealed that men and women were more likely to adopt CA by ripping and CA basins respectively from among the various variants of CA being promoted by Conservation Agriculture Project (CAP).…”
Section: Literature Reviewsupporting
confidence: 82%
“…Benefits of CA are realized upon simultaneous application of all principles of CA (Giller et al., ). However, ‘ideal’ CA is rarely practiced in smallholder farming systems of Zimbabwe (Pedzisa et al., ), southern Africa (Zira, Ignacio, Munyaradzi, & Nyamangara, ) and Africa in general (Giller et al., ).…”
Section: Discussionmentioning
confidence: 99%